Six Years of Experimental Investigation on Corrosion Resistance of Concrete with Corrosion Inhibitors (International Journal of Current Engineering and Technology, 2014)
Much time and effort has gone into the development of the corrosion inhibitors process. Corrosion undermines the physical integrity of structures and can lead to destruction of property and loss of life. Corrosion inhibitors are one means of protection for reinforced concrete structures. This investigation was carried out to evaluate long-term effect of corrosion inhibitors for concrete specimens made of ordinary and sulfate-resistant cement. Three commercial corrosion inhibitors were evaluated in this study: two anodic inhibitors based on calcium nitrite in both powder and liquid form, and mixed inhibitor reactions (anodic and cathodic reaction) based on nitrogen containing organic and non-organic substances. Three dosages of each type of corrosion inhibitors and two types of cement were considered in this study. Corrosion test was conducted using cylindrical specimen of 75 mm diameter and 150 mm length, with a high tensile strength deformed steel bar of 12 mm diameter. Test specimens were subjected to weekly wetting (in salt solution) and drying cycles for 3 years and kept dry for other 3 years. The whole testing period was 2244 days. Corrosion was monitored by obtaining half-cell potentials of the embedded steel. Results indicated that the addition of anodic corrosion inhibitor based on calcium nitrite with the producer recommendation dosage to OPC or SRC concrete have an insignificant effect on the corrosion potentials throughout the whole testing period. The use of corrosion inhibitors based on calcium nitrite and mixed reaction corrosion inhibitors based on nitrogen containing organic and non-organic substances decreases the percentage of steel weight loss for OPC concrete.
Keywords: Anodic inhibitors, mixed reaction, cathodic reaction, corrosion potentials, protection.